Family background, education, and earnings: The limited value of "test-score transmission" - Naomi Friedman-Sokuler; Moshe Justman (Global Labor Organization (GLO), 2024)
Even the most egalitarian education systems employ high-stakes tests to regulate the transition from universal secondary education to selective academic programs that open doors to skilled, well-paid professions. This gives parents a strong incentive to invest substantial resources in improving their children's' achievement on these tests, thus reinforcing dynastic socioeconomic advantage through "test-score transmission". Using longitudinal administrative data to follow Israeli students in Hebrew-language schools from eighth grade to age 29, we provide evidence that despite Israeli schools being publicly financed and tuition-free, test-score transmission is very much prevalent. Second-generation (SG) students with more educated and affluent parents do much better on the screening tests that regulate access to the most selective tertiary academic programs than first-generation (FG) students with similar eighth-grade test score ranks. Yet this advantage does not manifest itself in earnings differentials at age 29, controlling for eighth grade achievement, which are statistically insignificant or even reversed. This is consistent with eighth-grade test scores reflecting individual human capital; SG parents investing in their children's test-taking abilities and improving their access to selective tertiary programs; and employers not valuing these skills and compensating employees according to their observed productivity. Both men and women exhibit these patterns.
Keywords: I24; I26; J24; J62; 330; Intergenerational mobility; test-score transmission; human capital; parental education